RELEVANSI PEMIKIRAN ABU YUSUF DALAM KITAB AL-KHARAJ TERHADAP PERHITUNGAN PAJAK MODERN SERTA PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK - Supriadi; Luluk Mukaromah; M Dedy Eko Trisyono Safari; Hevi Susanti; Ayu Rachmawati (JAMER : Jurnal Akuntansi Merdeka, 2025)
This research explores the extent to which Abu Yusuf’s ideas in Al-Kharaj relate to contemporary taxation practices, particularly those involving the principles of justice, public benefit, trustworthiness, and the avoidance of excessive tax burdens on society. The study also investigates public perceptions of modern tax calculation systems and examines how Abu Yusuf’s values may influence taxpayer compliance today. Employing a qualitative method supported by open-ended questionnaires, this study seeks to capture respondents’ subjective interpretations and lived experiences regarding the current tax system. The findings reveal that Abu Yusuf’s taxation concepts remain highly relevant within Indonesia’s modern fiscal context, especially in promoting fairness and accountability in the management of public funds. Although modern tax regulations have been crafted to reflect these principles, practical obstacles remain, including perceptions of unequal public services, limited digital literacy, and a sense that tax obligations are not always distributed equitably. Furthermore, the results indicate that moral values, trust in governmental institutions, and the ethical conduct of tax officials significantly shape voluntary taxpayer compliance. These insights underscore the importance of consistently upholding justice, transparency, and responsible governance to enhance public adherence to tax obligations.